Oxford illustrated dictionary of 19th century language (Oxford : Oxford University Press, 2018)
This dictioinary unravels the intriguing, fascinating, and rich language of the most studied 19th century texts with clear explanations for unusual words, unfamiliar spellings, dialect and expressions.
Primary
Keywords: English language -- Dictionaries -- 19th century